2018
DOI: 10.1021/acsami.8b16601
|View full text |Cite
|
Sign up to set email alerts
|

New Helicene-Type Hole-Transporting Molecules for High-Performance and Durable Perovskite Solar Cells

Abstract: Three azahelicene derivatives with electron-rich bis(4-methoxyphenyl)amino or bis(p-methoxyphenyl)aminophenyl groups at the terminals were deliberately designed, synthesized, and characterized as hole-transporting materials (HTMs) for perovskite solar cells (PSCs). Optical and thermal properties, energy level alignments, film morphologies, hole extraction ability, and hole mobility were studied in detail. PSCs using the newly synthesized molecules as HTMs were fabricated. A maximum power conversion efficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 104 publications
(39 reference statements)
1
50
0
Order By: Relevance
“…To solvet his problem and to furthers tudy the relationship between HTMs tructure and device performance, new organic small molecules with appropriate energy levels andf avorable hole-transporting ability wered evelopedt or eplace spiro-OMeTAD. [16][17][18][19][20][21][22][23] The selection of the core structure is of great concern for designing organic small-molecule-based HTMs. In recenty ears, as eries of HTMs with phenothiazine, [24] acridine, [25] benzo [1,2- [26] truxene, [27] tetraphenylethylene, [28] and others as the core structures were reported.…”
Section: Introductionmentioning
confidence: 99%
“…To solvet his problem and to furthers tudy the relationship between HTMs tructure and device performance, new organic small molecules with appropriate energy levels andf avorable hole-transporting ability wered evelopedt or eplace spiro-OMeTAD. [16][17][18][19][20][21][22][23] The selection of the core structure is of great concern for designing organic small-molecule-based HTMs. In recenty ears, as eries of HTMs with phenothiazine, [24] acridine, [25] benzo [1,2- [26] truxene, [27] tetraphenylethylene, [28] and others as the core structures were reported.…”
Section: Introductionmentioning
confidence: 99%
“…As such, a semiconducting behavior was anticipated for the former helicene in the solid thin‐film state. Indeed, an apparent hole‐transporting property was demonstrated in a field effect transistor (FET) characteristics measurements, a hole mobility being found 1.5×10 −5 cm 2 /Vs (Figure S24) [11f] . The HOMO level estimated by photoelectron yield spectroscopy (PYS) measurement was −5.70 eV (Figure S25), which is in accord with the calculated one (−5.38 eV) at the B3LYP/6‐31G(d) level of theory (Figure S23).…”
Section: Methodsmentioning
confidence: 94%
“…As for the construction of azahelicenes containing a pyrrole‐type nitrogen, a carbazole skeleton is often employed and typically located in the center of helicene molecules (Scheme 1a, Cz‐helicene), [5g,11a–e] while some related less symmetrical azahelicenes have been known [11f–i] . On the other hand, we have been interested in indolo[3.2.1,‐ jk ]carbazole as another carbazole motif (Scheme 1b, ICz), [12] as the derivatives of ICz are highly fluorescent and can also be appended with donor moieties to form D‐π‐A‐type dyes for applications in dye‐sensitized solar cells [13] and host materials for phosphorescent organic diodes [14] .…”
Section: Methodsmentioning
confidence: 99%
“…Also, the rigidity and twisting induced by the helical scaffold are considered to be favorable for the phase stability (Jhulki et al., 2016). Compared with the triangular pyramid configuration of spirobifluorene in spiro-OMeTAD, the relative planarity of helicene (Lin et al., 2018) may enhance the hole mobility. Our preliminary studies have shown that PSCs with O5H-OMeDPA as HTL present a high PCE of 21.03% and good stability under continuous full-sunlight soaking at 60°C.
Figure 1Molecular Structure, Molecular Packing, and Energy Band(A) Chemical structure of O5H-OMeDPA.(B) Optical microscopic image of an O5H-OMeDPA single crystal.(C and D) Crystal structures along the a axis view (C) and the b axis view (D), with color-coded molecules: blue, enantiomer P ; red, enantiomer M .(E) DFT-calculated vcalence band structure of the O5H-OMeDPA single crystal.
…”
Section: Introductionmentioning
confidence: 99%